Lista de Cladóceros dulceacuícolas del Perú - Villar, Rubén S. Valdivia (Amazoniana, 1988)
Seventy six species of Cladocera are recorded in the present study, of which, 31 are new to the Peruvian fauna. Five species, Alonella nana, Ephemeroporus acanthodes, Alona cf. karelica, Indialona ganapati, and Daphniopsis sp., has never been recorded before in South America. The distribution of the various species in the different water bodies of Peru is given.
Keywords: Cladocera